Découverte de la statue d’une divinité antique remployée dans le baptistère de Brioude (Haute-Loire) : une représentation de Cernunnos ? - Fabrice Gauthier (Revue Archéologique du Centre de la France)
A piece of stone sculpture, found reused in a wall belonging to the baptistery of Brioude (Haute-Loire, France), represents a person sitting and holding a basket of fruit. Next to him are a deer and a bull. Our study reveals a snake with a sheep's head wound around his waist. This composition leads us to the identification of Cernunnos as the main figure of this sculpture. This identification enables us to see the origins of the early christian sanctuary in a new light.